RESPON PADI TRANSGENIK CV. NIPPONBARE GENERASI T1 YANG MENGANDUNG GEN Oryza sativa DEHYDRATION-RESPONSE ELEMENT BINDING 1A (OsDREB1A) TERHADAP CEKAMAN SALINITAS - Tri Joko Santoso; Aniversari Apriana; Atmitri Sisharmini; Kurniawan Rudi Trijatmiko (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Salinity is one of the abiotic constraints in the cultivation of rice crop. One of the reasons agricultural land becomes saline is due to the intrusion of seawater into the mainland as a result of global climate change. Dehydration-responsive element binding (DREB) gene is a plant -specific transcription factor gene that have important role in regulating plant responses to abiotic stresses, including high salinity. Transgenic rice plants cv. Nipponbare carrying OsDREB1A gene have been generated. However, study of the response of putative transgenic plants to salinity has not been done. The research objective is to study the response of T1 generation Nipponbare-OsDREB1A transgenic rice plants to salinity stress. The result showed that the response of putative transgenic rice Nipponbare-OsDREB1A to salinity stress 25 mM and 150 mM NaCl indicated a level of tolerance varies from highly sensitive to highly tolerance. These variations were possibly occurred because of the segregation state of the T1 generation transgenic rice. Based on damage symptom scoring and PCR analysis provided information that transgenic rice plant cv. Nipponbare-OsDREB1A which showed positive PCR had a very high tolerance to salinity stress 150 mM compared with non-transgenic rice cv. Nipponbare.